Medical tactic in hand polydactyly in children - Sedykh, Oleksandr; Paschenko, Yury; Piontkovska, Oksana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Untimely correction of anomalies of fingers and hands or inefficiently performed reconstructive operations may affect the processes of adaptation of children to life. Objective: To improve outcomes in children with polydactyly by optimizing the methods of surgical correction of congenital hand pathology. Methods: During the period from 2000 to 2012 in 118 patients (70 boys, 48 girls, age to 6 years) with polydactyly there were performed 141 operations on 136 hands. There were 68 children with radial form of polydactyly, 17 with ulnar form, and 3 with central one. For establishment of the nature of the pathology examination with using of radiological, CT, and ultrasound dopplerography mapping was done. Results: In the case of the main finger deformity after removal of additional finger we performed corrective osteotomies, modeling resections of articular surfaces, and restored capsular-ligamentous apparatus. In cases of ulnar polydactyly with thickening of V metacarpal bone on the wide head of which there are two claw like little fingers we removed less developed one, cut off the abductor digiti minimi, restored lateral metacarpophalangeal ligament, fixed the muscle to the proximal phalanx, angular deformity of the V finger we eliminated by wedge osteotomy with K-wire fixation. In cases of central polydactyly after removal of extra finger we used created from a remote segment reserve of skin for closing the skin defect on lateral surfaces of the fingers with simultaneous correction of axial deformities. Long-term outcomes were followed up during the period of 1 to 10 years in 78 children: good results were obtained in 44 cases, satisfactory — in 27, and unsatisfactory — in 7 cases. Errors and complications: deviation of the main finger, nonunion of bone surfaces, scar deformities, limitation of movement. Conclusions: While choosing the method of surgery and duration of its execution one should establish the primary and the secondary fingers in cases of radial polydactyly. Zigzag incisions, rational skin, bone and tendon plasty allow to prevent the formation of scar contractures and secondary deformities of fingers and contribute to the restoration of the hand function.